Risk factors for head and neck cancer in young adults: a pooled analysis in the INHANCE consortium - Toporcov, Tatiana Natasha; Ramroth, Heribert (International journal of epidemiology, 2015)
Abstract. Background: Increasing incidence of head and neck cancer (HNC) in young adults has been reported. We aimed to compare the role of major risk factors